All Days 2000
DOI: 10.2118/59363-ms
|View full text |Cite
|
Sign up to set email alerts
|

Alkali / Surfactant / Polymer at VLA 6/9/21 Field in Maracaibo Lake: Experimental Results and Pilot Project Design

Abstract: The VLA 6/9/21 Field is a waterflooded light crude oil reservoir located in Maracaibo Lake, West Venezuela. In the last two years PDVSA E & P has developed Integrated Laboratory Fields (ILF) as a strategy to evaluate new technologies and EOR methods in order to improve light and medium oil recoveryfactors. Alkali/Surfactant/Polymer (ASP) is one of the chemical flooding technologies that has recently been evaluated in Venezuela. The objetive of this study is to describe the followed method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Vargo et al (1999), Wang et al (1999), Manrique et al (2000) and many other researchers have also reported successful ASP field tests. Gao and Gao (2010) documented the test results of different ASP flooding at Karamay, Daqing and Shengli fields.…”
Section: Alkaline-surfactant-polymer (Asp) Floodingmentioning
confidence: 93%
“…Vargo et al (1999), Wang et al (1999), Manrique et al (2000) and many other researchers have also reported successful ASP field tests. Gao and Gao (2010) documented the test results of different ASP flooding at Karamay, Daqing and Shengli fields.…”
Section: Alkaline-surfactant-polymer (Asp) Floodingmentioning
confidence: 93%
“…• If we could eliminate the uncertainty of one or more of the input variables which ones should be chosen (variable selection for maximum uncertainty reduction)? Previously reported works using reservoir numerical simulation have been limited to local sensitivity analyses (Wu, 1996;Zhijian et al, 1998;Manrique et al, 2000;Qi et al, 2000;Hernández et al, 2001) and global but discrete analyses -factorial designs (Delshad et al, 2005). The latter approach given its discrete nature may hide the true nature of the process behavior or may require an unaffordable amount of experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional approaches for the optimization of ASP flooding processes have been limited to a trial and error method or local sensitivity analysis using reservoir numerical simulation [6][7][8][9][10] , where formal optimization is seldom used because of the computationally expensive objective function evaluations (i.e., numerical reservoir simulator model). The surrogate-based optimization approach has been shown to be useful in the sensitivity analysis and optimization of computationally expensive simulation-based models in the aerospace [11][12][13] , automotive 14,15 , and oil industries [16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%